E.V. From ‘Greater’ to ‘Global Britain’: The New and the Old in the Foreign Policy of the United Kingdom - E. V. Khakhalkina (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2023)
The UK withdrawal from the European Union forced the country to reevaluate its relations with the outer world. These political and ideological searches culminated in the concept of Global Britain. At the same time, they have drawn attention of the academic community to similar intellectual endeavors at the turn of the 19th-20th centuries, when British politicians also faced the need for a qualitative reassessment of the empire’s place in the world. In this context historical references can both help to place the concept of Global Britain within a broader ideological and political framework and shed light on some of its less obvious aspects. And it is particularly interesting to compare it with the concept of Greater Britain, which was extensively discussed during that period. The first section of the paper identifies the origins of the Greater Britain concept, as well as its key provisions. The author notes that the idea of ‘Greater Britain’, aiming to create a sort of federation that would bring together the metropole and the dominions, emerged as a response to growing centrifugal tendencies within the British Empire and intensification of colonial rivalry between the great powers. The second section outlines the conceptual core of the ‘Global Britain’, which involves expanding the scope of the UK foreign policy opportunities after leaving the European Union by establishing a more active interaction with countries and regions that were once part of the empire. The paper emphasizes the migration factor, which served as a fundamental element of the British statehood in various periods of its history and became an integral part of the British political identity. The author argues that there is a certain continuity in the ideological and philosophical content of the two concepts, which were both formulated in similar conditions, both originated from the search for new guidelines for the UK policy in a changing world. However, these concepts shouldn’t be confused. Whereas ‘Greater Britain’ was aimed at consolidating the crumbling empire, ‘Global Britain’ is intended primarily to bridge various divides across the society, which in turn implies re-examination of the UK national identity in general. The author concludes that the concept of Global Britain in its current form cannot address these issues, on the contrary, it rather epitomizes the lack of innovative ideas and solutions among contemporary British elites.